(untitled) (Innovative professional education, 2024)
Career counseling is provided with the aim of identifying competencies, abilities, and motivation of education seekers, young and experienced professionals for forecasting further professional and career development. It allows you to assess professionally important qualities and to focus on those positions and industries where they will be most in demand and successful. Career counseling based on the results of the test can be used in the Employment Assistance Centers for students and graduates, in the personnel selection departments.